Democracy: The unfinished journey, 508 BC to AD 1993 (Oxford Univ, 1992)
The book explains how a casual practical solution to local Greek political difficulties so very long ago has come to stand virtually unchallenged as the ground for modern political authority. It shows how the idea of democracy has kept its power in a world which is utterly different from the world of classical Greece and how the questions which the greeks first raised about the meaning of democratic rule still loom overhuman political and economic institutions in a setting in which no modern population can ever rule in practice, day by day, as the Athenian demos ruled. By viewing its astonishing history across this great arc of time, the book shows why democracy today has both the power and the vulnerability which make it the key to understanding politics; and it explains why it has triumphed so decisively in the modern world